Historical and contemporary opportunities to assert social work's political commitment between private and public sphere - Walter Lorenz (Social Work & Society, 2024)
The Corona pandemic evidenced the profound uncertainties over whether securing one's welfare is a private or a public concern since neoliberal policies had promoted individualisation and privatisation on all fronts. This historical overview of key moments in the development of social work summarises the transformative role this profession assumed in the face of political tendencies to impose splits between a national and an international orientation, scientific neutrality and the recognition of diverse identity claims, personal and public responsibility, care and control. Overcoming these dilemmas requires an ethical commitment in giving situation-specific assistance and a political commitment towards building a public sphere that can effectively raise personal concerns in terms of public and indeed international rights. In this way social work can contribute to trust-building in participatively and reflectively grounded expertise and thereby the strengthening of democratic processes.